1997
DOI: 10.1086/301604
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Characterization and Genotype-Phenotype Correlation in Barth Syndrome

Abstract: Barth syndrome is an X-linked cardiomyopathy with neutropenia and 3-methylglutaconic aciduria. Recently, mutations in the G4.5 gene, located in Xq28, have been described in four probands with Barth syndrome. We have now evaluated 14 Barth syndrome pedigrees for mutations in G4.5 and have identified unique mutations in all, including four splice-site mutations, three deletions, one insertion, five missense mutations, and one nonsense mutation. Nine of the 14 mutations are predicted to significantly disrupt the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
110
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 16 publications
3
110
0
1
Order By: Relevance
“…PCR products digested with SfaNI showed that the patient was hemizygous for the R94S mutation. The mother of the patient was heterozygous same position (R94C) has been previously reported (Johnston et al 1997). These data suggest that R94S is not a common polymorphism, but a disease-causing mutation.…”
Section: Resultssupporting
confidence: 68%
“…PCR products digested with SfaNI showed that the patient was hemizygous for the R94S mutation. The mother of the patient was heterozygous same position (R94C) has been previously reported (Johnston et al 1997). These data suggest that R94S is not a common polymorphism, but a disease-causing mutation.…”
Section: Resultssupporting
confidence: 68%
“…Respiratory chain abnormalities, reported in other patients with X-linked DCM (Barth et al, 1983(Barth et al, , 1996, were not found in our patients. Relating genotype to phenotype has been difficult previously (Cantlay et al, 1999;D'Adamo et al, 1997;Johnston et al, 1997) and remains difficult today.…”
Section: Discussionmentioning
confidence: 99%
“…lished missense mutations, 7 occur in these motifs. Mutations V183G and G197E have been found repeatedly (Bleyl et al, 1997;Cantlay et al, 1999;D'Adamo et al, 1997;Ichida et al, 2001;Johnston et al, 1997;Neuwald, 1997). The significant clustering of over one-half the reported disease-causing mutations in putative acyltransferase motifs (p Ͻ 0.022, 2 test) may reveal regions of the tafazzin protein critical for its function.…”
Section: Mutations In Gene G45mentioning
confidence: 99%
See 1 more Smart Citation
“…Complex I structural subunits [151], B17.2L & NDUFAF1 [151], SDHA [152], SDHC [153], SDHD [153], BCS1L [154,155], SURF1 [156], SCO1 [157], SCO2 [158], COX10 [159], COX15 [160,161], ETHE1 [162], LRPPRC (LSFC) [138], ATP12 [163], PDSS1 [164], PDSS2 [165], COQ2 [164], APTX [166], ADCK3 [167], ETFDH [168], TSFM [169], TUFM [170], EGF1 [170], MRPS16 [171], PUS1 [172], DARS2 [173], PDHA1 [14], POLG1 [107], TK2 [174,175], DGUOK [176], MPV17 [137], SUCLA2 [177],SUCLG1 [177],RRM2B [178], TWINKLE [179], ANT1 [180], ABC7 [181], FXN [182], OPA1 [183], DDP1 [184], SPG7 [185,186], TAZ [187] …”
mentioning
confidence: 99%